The financial reporting of the National Fisheries Corporation of Tuvalu: The case for alternative indigenous reporting mechanisms - Brown, Alistair (Pergamon, 2018)
© 2017 Elsevier Ltd Through textual analysis, the study examines the Indigenous financial reporting compliance of the National Fisheries Corporation of Tuvalu for the years-ending 2007–2014. The results reveal that over the sample period the corporation did not report at all. This is despite the fact that the corporation was under a duty to report through five Indigenous sets of enactments and received a substantial guaranteed loan from the National Bank of Tuvalu to develop its joint ventures with foreign fisheries fleets. There appears little evidence that the corporation has benefitted from technical reporting assistance from foreign experts over a long period of time even though Tuvalu has received substantial monetary and in-kind assistance from foreign donors. The study suggests the use of alternative Indigenous reporting mechanisms to encourage improved reporting by the corporation.